Quantitative Phytochemical Profile and Antioxidant Properties of Ethyl Acetate Extracts of (Baker) and (Fresen) - Paul Nyalo Msc; George Omwenga PhD; Mathew Ngugi PhD (SAGE Publishing, 2023)
Overproduction of free radicals in excess of antioxidants leads to oxidative stress which can cause harm to the body. Conventional antioxidants have drawbacks and are believed to be carcinogenic. The present study seeked to confirm folklore use and validate the antioxidant potentials of Grewia tembensis and Xerophyta spekei which have been widely used in the Mbeere community as medicinal plants. Antioxidant properties were determined through scavenging effects of diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide radicals as well as iron chelating effects. The data obtained was assayed in comparison to the standards (Ascorbic acid and EDTA). Ascorbic acid had a significantly greater DPPH radical scavenging property with an inhibitory concentration (IC 50 ) value of 20.54 ± 2.24 µg/mL in comparison to the plant extracts, which had IC 50 values of 33.00 ± 1.47 µg/mL, 69.66 ± 1.01 µg/mL and 86.88 ± 2.64 µg/mL for X. spekei, G. tembensis leaf and G. tembensis stem bark extracts, respectively. EDTA demonstrated a significantly greater iron chelating effect having a significantly lesser IC 50 value of 25.05 ± 0.79 µg/mL as opposed to 43.56 ± 0.46 µg/mL, 89.78 ± 0.55 µg/mL, and 120.70 ± 0.71 µg/mL for X. spekei, G. tembensis leaf, and G. tembensis stem bark extracts respectively. Additionally, ascorbic acid also exhibited stronger hydrogen peroxide radical scavenging effect than the studied extracts. Generally, X. spekei extract had higher antioxidant activities as compared to both the leaf and stem bark extracts of G. tembensis . The phytochemical screening demonstrated the presence of secondary metabolites associated with antioxidant properties. The present study therefore, recommends ethno medicinal and therapeutic use of G. tembensis and X. spekei in the treatment and management of oxidative stress related infections.